REMOTE WAYS TO CONTROL WATER DEPTH ON THE RUNWAY SURFACES - Kryvenko, Julij (Proceedings of National Aviation University (archive), 2016)
In the article are provided the findings on the water draining from the runway surface obtained with the use of an automatic remote water depth sensor. The results obtained enable improvement of water depth control, increase safety, and aerodrome capacity.